Prospective observational study of oxidative stress in the pathology of benign prostatic hyperplasia with bladder diverticulum - Shuijing Yin; Yu Qiu (PLoS ONE, 2025)
Background Oxidative stress contributes to benign prostatic hyperplasia (BPH) pathogenesis, but its role in BPH with bladder diverticulum is unclear. Methods This prospective cohort study compared 126 BPH patients at the Second Hospital of Harbin Medical University. The study involved two groups (n = 63 for each group): group A, comprising patients with BPH, and group B, consisting of BPH patients with bladder diverticulum. Ultrasound imaging and CT scans were employed to assess the features of BPH and bladder diverticulum, respectively. Various clinical parameters and oxidative stress biomarkers were compared between the groups. Results Group B exhibited significantly higher creatinine (101.8 ± 27.6 µmol/L vs. 56.1 ± 23.6 µmol/L, p < 0.0001), WBC counts (7.0 ± 1.9 vs. 4.2 ± 1.3 × 10⁹/L, p < 0.0001), residual urine volume (400.1 ± 252.0 mL vs. 150.7 ± 93.9 mL, p < 0.0001), and oxidative stress markers, including 8-OHdG (1.93 ± 0.58 vs. 1.70 ± 0.73 ng/mg creatinine, p = 0.014) and MDA (2.46 ± 0.57 vs. 2.03 ± 0.57 μmol/L, p < 0.0001). In group A, 8-OHdG positively correlated with residual urine volume (rho = 0.68) and nitric oxide with bladder wall thickness (rho = 0.70), while quality of life (QoL) negatively correlated with nitric oxide (rho = -0.76). In group B, oxidative stress markers correlated positively with BMI (e.g., homocysteine, rho = 0.69) and bladder wall thickness (e.g., nitric oxide, rho = 0.69), with QoL negatively correlated with uric acid (rho = -0.78). Conclusions Bladder diverticulum in BPH patients is associated with elevated oxidative stress, increased inflammation, and impaired bladder function.